2016
DOI: 10.1007/s12199-016-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

The associations between lifestyles and mental health using the General Health Questionnaire 12-items are different dependently on age and sex: a population-based cross-sectional study in Kanazawa, Japan

Abstract: The associations between mental health and lifestyles differ across age groups. Further study is needed to reveal effects of aging on lifestyle and mental health with a longitudinal design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
3
21
1
Order By: Relevance
“…Our study was conducted in only two geographical areas in Japan. However, a previous crosssectional community-based study in Kanazawa, Japan, reported a GHQ score ≥ 4 in 24.2% of men (n = 4693; mean age 51.6 ± 19.5 years) and 32.0% of women (n = 5678; mean age 52.4 ± 19.4 years) [44]. These percentages were close to ours, which suggests that our findings may be generalizable to the Japanese adult populations.…”
Section: Discussionsupporting
confidence: 88%
“…Our study was conducted in only two geographical areas in Japan. However, a previous crosssectional community-based study in Kanazawa, Japan, reported a GHQ score ≥ 4 in 24.2% of men (n = 4693; mean age 51.6 ± 19.5 years) and 32.0% of women (n = 5678; mean age 52.4 ± 19.4 years) [44]. These percentages were close to ours, which suggests that our findings may be generalizable to the Japanese adult populations.…”
Section: Discussionsupporting
confidence: 88%
“…This study has some limitations, first, due to the limitation of data acquisition, it is difficult to evaluate other factors that may have an impact on their mental health, such as their lifestyle habits (exercise, sleep) [34]. Second, we did not have a comprehensive understanding of the physical health status of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, higher life satisfaction lowers the risk of mental health (D'Ambrosi et al , ; Hannaford, Moore, & Macleod, ). A study from Japan showed the worst mental health status in middle‐aged and young persons (Hori et al , ). The present study discovered that the GHQ‐12 Scale evaluation for health was significantly associated with life satisfaction.…”
Section: Discussionmentioning
confidence: 99%